AKULTURASI BUDAYA ETNIS BELANDA DALAM MAKANAN NUSANTARA PERKEDEL - Riska Azikia Windiany; dinda reza okky naWa; Supriyono (Universitas PGRI Adi Buana Surabaya, 2023)
Indonesia as a society is known for its cultural diversity such as traditional practices and customs. Some of them are historically influenced by colonialism. Just like Indonesia, which experienced a long colonial period under Dutch rule and left a big influence on aspects of people's lives and culinary delights in Indonesia. One of the Indonesian foods that were influenced by Dutch culture is Frikadeller. Frikadeller in Indonesia means